Evaluation of Diagnostic Accuracy and Therapeutic Approach of Dermatologists and Plastic Surgeons to Non-Melanocytic Skin Lesions by Using Telemedicine - Burcu Tugrul; Basak Yalici-Armagan; Hatice Gamze Demirdag; Ozge Gunduz (Mattioli1885, 2022)
Background: In the new circumstances of Coronavirus disease 2019 pandemic, teledermatology and teledermoscopy have become more important in daily practice for departments which visuality is at the forefront as dermatology and plastic and reconstructive surgery. Objective: In this study, it is aimed to determine diagnostic accuracy and treatment approaches of non-melanocytic skin lesions between two clinics by store and forward teledermatology method and to evaluate the contribution of teledermoscopy to the diagnostic accuracy of dermatologists. Methods: A total of 26 patients with non-melanocytic skin lesions were included to the study. Clinical images of the lesions were sent by email to three plastic surgeons and three dermatologists. The accuracy of the diagnoses were evaluated by comparing teledermatology with histopathology. Diagnosis and treatment approaches were recorded for both clinics. Dermatologists also defined their diagnosis with teledermoscopic images. Results: The mean percentage of diagnostic accuracy among dermatologists' was 74.3% and among plastic surgeons' was 61.5%. There was no significant difference in diagnostic accuracy between departments (p=0.625). There was a statistically significant difference between the departments for diagnostic and treatment approaches (p values respectively p=0.002, p<0.001). Plastic surgeons prefered to confirm their pre-diagnosis histopathologically more than dermatologists. Plastic surgeons recommended surgical procedures for 25 lesions (96.2%) while dermatologists for 14 (53.8%) lesions. Teledermoscopy increased the rate of diagnostic accuracy of dermatologists from 74,3% to 82%. Conclusions: Teledermatology is an effective method for non-melanocytic skin lesions with high diagnostic accuracy. Adding dermoscopy to teledermatology increases diagnostic accuracy of dermatologists on non-melanocytic skin lesions.